2019
DOI: 10.1186/s12936-019-2679-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and sociodemographic factors associated with household malaria burden in the Congo

Abstract: Background Malaria is one of the most severe public health issues that result in massive morbidity and mortality in most countries of the sub-Saharan Africa (SSA). This study aimed to determine the scope of household, accessibility to malaria care and factors associated with household malaria in the Democratic Republic of Congo (DRC). Methods This was a community-based cross-sectional study conducted in an urban and a rural sites in which 152 households participated, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
(25 reference statements)
1
34
0
Order By: Relevance
“…This allows us to make inferences regarding the country as a whole. Other recent malaria risk factor studies have fewer individuals or are conducted in a smaller geographic area 11,12 . Second, we determined malaria infection using high-throughput real-time PCR, the most sensitive method for diagnosing infection 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows us to make inferences regarding the country as a whole. Other recent malaria risk factor studies have fewer individuals or are conducted in a smaller geographic area 11,12 . Second, we determined malaria infection using high-throughput real-time PCR, the most sensitive method for diagnosing infection 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies performed in the DRC have identified important risk factors for infection 4,9,10 . These studies showed that increasing age, wealth, and individual bed-net use are protective, as are increasing community level bed-net use, lower average temperature and higher altitude [9][10][11][12] . However, these studies included only children under the age of five 9,10 , or were small and geographically limited 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] The environmental and socio-demographic factors predominantly affect the burden of malaria at household level. 11 Ethiopia has made notable progress in decreasing the prevalence and burden of malaria through public health measures taken during the millennium development goals (MDGs) era. 12 However, malaria remains one of the public health problems with a high level of mortality and disability adjusted life years (DALYs).…”
Section: Introductionmentioning
confidence: 99%
“…Our pilot survey conducted in Congolese rural and urban counties showed that poor WASH and low income were associated with malaria [13]. Furthermore, other previous works showed evidence on the effects of malaria on workers' absenteeism, productivity, medical costs [14,15], population growth, as well as children developmental retardation and premature death [16,17].…”
Section: Introductionmentioning
confidence: 99%